¿Does evolution violate the second law of thermodynamics? - Sánchez-Véliz, Diego (2025)
The argument that evolution contradicts the second law of thermodynamics arises from a misinterpretation of this law, which does not preclude local increases in order in open systems such as the Earth or living organisms. The second law states that total entropy in an isolated system tends to increase, but it does not exclude the possibility that complexity may increase locally provided it is compensated by a larger increase in entropy in the environment. Evolution and abiogenesis operate within the limits of physical laws. Energy from the Sun drives self-organizing processes, allowing living systems to reduce their internal entropy while increasing the total entropy of the universe. Furthermore, concepts such as Gibbs free energy and dissipative structures explain how biological and chemical processes can generate order without violating thermodynamics. Recent studies connect natural selection with thermodynamic principles, showing that evolution maximizes energy efficiency and complies with the second law. Far from contradicting each other, evolution and thermodynamics are interdependent, and understanding them together reveals how living systems emerge and organize in a universe governed by physical laws.